TOKSISITAS AKUT (LC50) SERBUK BOR (Cuttings) TERHADAP Daphnia sp. - Effendi, Hefni; Emawan, Aditya Herry; Wardiatno, Yusli; Krisanti, Majariana (Bumi Lestari, 2012)
Research was aimed at determining toxicity of drilling cuttings towards Daphnia , revealed in LC 50 96 hours, meaning that cuttings concentration cause 50% population of Daphnia within the period of 96 hour observation. LC 50 96 hour is utilized for preliminary strategy of managing drilling cuttings. Static test was applied at the main bioassay experiment.  Mortality was as an indicator of toxicity.  Bioassay experiment refers to US-EPA (1991, 1996, 2002); Ziehl and Schmitt (2000).  Mortality and water quality fluctuation were observed at hours 2, 4, 6, 8, 24, 48, 72, and 96. Determination of LC 50 96 hour was carried out by the method of Probit Analysis.  Manual count and software EPA Probit Analysis Version 1.5 were applied. LC 50 96 hours cuttings towards Daphnia is 22.177 - 22,208 ppm.  This indicates that cuttings has almost non-toxic characteristic.  However, disposal of these cuttings needs oil content measurement.  If oil content meets regulation (? 10%), cuttings is allowed to be discharged to the surrounding terrestrial environment.
Keywords: Toxicity; Daphnia; Cuttings; LC50 96 hour